Initial serum chloride is associated with all-cause mortality in critically ill patients with acute kidney injury - Dezhun Chen; Fengfeng Lu; Bihuan Cheng; Benji Wang (Renal Failure)
Objective Disorders related to serum chloride concentration have recently attracted considerable interest. We sought to determine whether initial serum chloride was associated with an increased risk of all-cause mortality among critically ill patients diagnosed with acute kidney injury (AKI).Methods We searched the Multiparameter Intelligent Monitoring in the Intensive Care IV database to retrieve clinical data, including demographic factors, clinical variables, lab tests, and scoring systems. Hypothesis testing was conducted using a range of statistical approaches, including the generalized additive model, the Cox proportional hazards model, and subgroup analyses.Results Our research included 19,107 participants who met the set criteria. We found that the levels of chloride in the patient’s serum upon admission had a similar inverted L-shaped relationship with the 30-day all-cause mortality rate in AKI. In multivariate analysis following the adjustment of confounders such as sex, ethnicity, and age, compared with the referent group (100–105 mmol/L), low-chloride (< 100 mmol/L) was a considerable risk predictor for 30-day, 90-day, and 365-day all-cause mortality. In particular, the HRs (95% CIs) for chloride were 1.49 (1.36, 1.63), 1.48 (1.36, 1.61), and 1.59 (1.47, 1.71). After adjusting additional clinical characteristics, low-chloride levels still served independently as a major predictor of all-cause mortality over 30 days, 90 days, and 365 days (HR, 95% CI: 1.24, 1.09–1.41; 1.17, 1.04–1.32; 1.27, 1.14–1.42).Conclusions The probability of all-cause mortality was higher in severely ill individuals with AKI who had lower baseline serum chloride levels upon admission to the intensive care unit (ICU).